استخدام النماذج الكمية في اتخاذ قرار التمويل برأس المال المخاطر - بوقرة, رابح; بن النوي, احلام (Université de M'sila, 2016)
This study aims to introduce capital technology risk financing technique developed in the United States mid-forties of the last century, specifically to finance innovative startups that do not qualify characteristics and specificities for conventional financing (banks, the stock market), and the risk of capital differs from these circumstances last in terms of his view of risk, the criteria adopted in the investment decision, the nature of the funding provided and the relationship that collects Balmpadr. In this study will be to address the financing of capital risk and reality in developed and developing countries, as we will discuss the importance of quantitative models in making funding decisions.
Keywords: venture capital, quantitative models, financing, investment projects emerging.